New results in $G$-best approximation in $G$-metric spaces - Dehghan, Nezhad A.; Mazaheri, H. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
The purpose of this paper is to introduce and discuss the concepts of G-best approximation and $a_0$ -orthogonality in the theory of $G$-metric spaces. We consider the relationship between these concepts and the dual $X$ and obtain some results on subsets of $G$-metric spaces similar to normed spaces.